2018
DOI: 10.1073/pnas.1718712115
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination can drive an increase in frequencies of antibiotic resistance among nonvaccine serotypes ofStreptococcus pneumoniae

Abstract: The bacterial pathogen is a major public health concern, being responsible for more than 1.5 million deaths annually through pneumonia, meningitis, and septicemia. Available vaccines target only a subset of serotypes, so vaccination is often accompanied by a rise in the frequency of nonvaccine serotypes. Epidemiological studies suggest that such a change in serotype frequencies is often coupled with an increase of antibiotic resistance among nonvaccine serotypes. Building on previous multilocus models for bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 69 publications
6
39
0
Order By: Relevance
“…However, recently published data on nasopharyngeal carriage as measured in a cross-sectional observational study in Blantyre (Southern Malawi), four to seven years after PCV13 introduction (2015)(2016)(2017)(2018), has shown that vaccine impact (VT carriage reduction) has been slower than expected and heterogeneous across age-groups 22 . Epidemiological mathematical models have previously been employed successfully to improve our understanding of pneumococcal dynamics 5,9,[23][24][25][26][27] , as well as having contributed to explain, estimate and project PCV impact 8,11,28 . The main advantage of models is their cost-free potential to test hypotheses and gain a mechanistic, ecological and immunological understanding of carriage and disease dynamics, estimating epidemiological parameters which are difficult to otherwise quantify from raw epidemiological data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently published data on nasopharyngeal carriage as measured in a cross-sectional observational study in Blantyre (Southern Malawi), four to seven years after PCV13 introduction (2015)(2016)(2017)(2018), has shown that vaccine impact (VT carriage reduction) has been slower than expected and heterogeneous across age-groups 22 . Epidemiological mathematical models have previously been employed successfully to improve our understanding of pneumococcal dynamics 5,9,[23][24][25][26][27] , as well as having contributed to explain, estimate and project PCV impact 8,11,28 . The main advantage of models is their cost-free potential to test hypotheses and gain a mechanistic, ecological and immunological understanding of carriage and disease dynamics, estimating epidemiological parameters which are difficult to otherwise quantify from raw epidemiological data.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of models is their cost-free potential to test hypotheses and gain a mechanistic, ecological and immunological understanding of carriage and disease dynamics, estimating epidemiological parameters which are difficult to otherwise quantify from raw epidemiological data. For example, models have successfully yielded estimates of VT and non-VT pneumococci transmission potentials 26,[29][30][31] , pneumococcal competition factors 8,9,23,28,32,33 and measures of vaccine-induced protection from carriage at the individual level 11,17,28,34,35 , none of which are readily observed or quantified in crosssectional observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…61 Although incompletely understood, the association of serotype replacement with antibiotic resistance has been attributed to elimination of competition by antibiotic-susceptible vaccine serotypes in the nasopharynx, enabling emergence of previously suppressed, resistant nonvaccine serotypes. 62 In this setting, antibiotic resistance comes at the expense of reduced fitness of these nonvaccine serotypes. 63 This may be overcome, however, via genetic transfer of metabolic and virulence components from vaccine to nonvaccine serotypes of the pathogen, conferring both fitness and persistence on the latter serotypes.…”
Section: Causes and Mechanisms Of Antibiotic Resistancementioning
confidence: 99%
“…However, it is unclear how universal vaccination may itself impact upon the evolution of antibiotic resistance in S. pneumoniae. While mathematical models are a useful tool for generating predictions from nonlinear transmission dynamics (15,16), existing models focus on serotype-specific vaccines and, even then, disagree over the expected impact of vaccination on resistance evolution (17)(18)(19)(20)(21)(22)(23). Comparing and interpreting the results of these models is hampered by the fact that none starts from a position of recapitulating contemporary, large-scale patterns of antibiotic resistance.…”
mentioning
confidence: 99%